PENGARUH PEMBERIAN MIKRO ORGANISME LOKAL (MOL) NASI DAN HORMON TANAMAN UNGGUL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum Annum L.) - Sarmi Julita; Hercules Gultom; Mardaleni Mardaleni (UIR Press, 2013)
The objective of this research was to examine the effect of giving Rice MOL and superior plant hormone on growth and yield of Chilli. The experiment was arranged using the completely randomized design with two factors. The first factor was rice MOL (M), namely M0 (without rice MOL), M1 (50 cc/l water), M2 (100 cc/l water), and M3 (150 cc/l water).The second factor was application of superior plant hormone (H), consisting of four factor, namely H0 (without hormone), H1(1 cc/l water), H2 (2 cc/l water), and H3 (3 cc/l water). The parameters observed were plant height, flowering age, the first harvest age, fruit weight per plant, fruit weight per plot, and number of remaining fruit. Data were analyzed using statistical technique and continuing test of BNJ at 5% confident level. The results showed that the interaction of giving rice MOL and hormone had a significant effect on flowering age and harvest age with the best treatment M2H2 with 56.67 days and M2H2 with 112.67 days, respectively. The rice MOL alone gave a significant effect on flowering age, the first harvest age, econmic fruit weight per plant, and economic fruit weight per plot with the best treatment was M2. The superior plant hormone alone affected significantly plant height, flowering age, the first harvested age, economic fruit weight per plant, economic fruit weight per plot, and number of remaining uneconomic fruit per plant with the best treatment of H2.